Piezoelectric ceramic material with high Curie temperature and high piezoelectric coefficient and preparation method thereof

By introducing Ca2+ and Sr2+, LiTaO3 and LaAlO3 into the bismuth layered piezoelectric ceramic material and using sintering aids, the Curie temperature and piezoelectric coefficient of the material are improved, and the problem of low piezoelectric coefficient in the prior art is solved. , achieving efficient piezoelectric performance improvement.

CN119285356AActive Publication Date: 2025-01-10HUNAN MEICHENG NEW MATERIALS TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411847080.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-01-10
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The existing bismuth layered piezoelectric ceramic materials have a low piezoelectric coefficient, which limits their wide application in high-end technology fields, especially in high temperature environments.

Method used

Using composite A-position metal ions Ca2+ and Sr2+, LiTaO3 and LaAlO3 are introduced, and transition metal oxides and lanthanide rare earth oxides are used as sintering aids to adjust the structure and performance of the material and improve the Curie temperature and pressure of piezoelectric ceramic materials. Electricity coefficient.

Benefits of technology

The piezoelectric coefficient of piezoelectric ceramic materials is significantly improved, with a maximum capacity of 35pC/N, and its stability and electrochemical properties at high temperatures are improved, and the density and microstructure of the ceramics are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285356A_ABST
    Figure CN119285356A_ABST
Patent Text Reader

Abstract

The invention relates to the field of piezoelectric ceramic materials, in particular to a piezoelectric ceramic material with high Curie temperature and high piezoelectric coefficient and a preparation method thereof, the structural formula of the piezoelectric ceramic material is as follows: (1-x-y) (Bi2O2) < 2 + > (Am-1BmO3m + 1) < 2-x > LiTaO3-yLaAlO3, A is any one or more of Na < + >, K < + >, Ca < 2 + >, Sr < 2 + >, Ba < 2 + >, Pb < 2 + >, Bi < 3 + > and La < 3 + >; b is any one or more of Fe < 3 + >, Ti < 4 + >, Nb < 5 + > and W < 6 + >; m is an integer between 1 and 4; 0 < x < = 0.2; 0 < y < = 0.2, the piezoelectric ceramic material prepared by the method has high Curie temperature and excellent electrochemical performance, the maximum piezoelectric constant can reach 35pC / N, and compared with the currently reported bismuth layered structure piezoelectric ceramic, the piezoelectric ceramic material has the advantage that the piezoelectric constant is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of piezoelectric ceramic materials, in particular to a piezoelectric ceramic material with high Curie temperature and high piezoelectric coefficient and a preparation method thereof. Background Art

[0002] Piezoelectric materials are an important type of functional materials with important applications in many fields of the national economy. In high-end technology fields such as energy, aerospace, and defense industry, the application of piezoelectric materials has shifted from conventional use to service in extreme environments, which requires piezoelectric materials and piezoelectric sensors to be able to operate at higher temperatures.

[0003] Bismuth layered piezoelectric ceramics have attracted widespread attention from researchers due to their special layered structure and high Curie temperature. However, current studies have found that the piezoelectric coefficient of prototype bismuth layered piezoelectric ceramics is generally only 5-20pC / N. The low piezoelectric coefficient limits its wide application. Summary of the invention

[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes a piezoelectric ceramic material with high Curie temperature and high piezoelectric coefficient and a preparation method thereof.

[0005] The technical solutions adopted are as follows: A piezoelectric ceramic material with high Curie temperature and high piezoelectric coefficient, the structural formula of the piezoelectric ceramic material is as follows: (1-xy)(Bi2O2) 2+ (A m-1 B m O 3m+1 ) 2- -xLiTaO3-yLaAlO3 Among them, A is Ca 2+ and / or Sr 2+ ; B is Nb 5+ ; m is an integer between 1 and 4; 0<x≤0.2; 0<y≤0.2; It also includes a sintering aid, which is a transition metal oxide and / or a lanthanide rare earth oxide; The transition metal oxide is manganese oxide and / or copper oxide; The lanthanide rare earth oxide is a composite of any one or more of cerium oxide, samarium oxide, and dysprosium oxide; The amount of the sintering aid is (1-xy)(Bi2O2) 2+ (A m-1 B m O3m+1 ) 2- -0.1-1% of the mass of xLiTaO3-yLaAlO3.

[0006] Furthermore, m is preferably 2.

[0007] Furthermore, when the sintering aid is a combination of transition metal oxide and lanthanide rare earth oxide, the performance of the piezoelectric ceramic material is optimal; Further, when the sintering aid is a combination of a transition metal oxide and a lanthanide rare earth oxide, the mass ratio of the transition metal oxide to the lanthanide rare earth oxide can be selected from 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, preferably 1:1; Furthermore, the amount of the sintering aid is (1-xy)(Bi2O2) 2+ (A m-1 B m O 3m+1 ) 2- -0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, and preferably 0.5% of the mass of -xLiTaO3-yLaAlO3.

[0008] Furthermore, the transition metal oxide is preferably copper oxide.

[0009] Furthermore, the lanthanide rare earth oxide is preferably cerium oxide.

[0010] Furthermore, A is preferably Ca 2+ and Sr 2+ , Ca 2+ and Sr 2+ The molar ratio of Ca can be selected from 1:1, 1:2, 1:3, 1:4, 2:1, 3:1, 4, 2+ and Sr 2+ The molar ratio is preferably 1:4.

[0011] Further, 0.05≤x≤0.15, 0.01≤y≤0.05; Furthermore, x=0.1, y=0.025.

[0012] The present invention also provides a method for preparing a piezoelectric ceramic material: Bi2O3, oxide A and oxide B are mixed, dried and pre-fired at 600-800℃ after ball milling once, and then mixed with LiTaO3, LaAlO3 and sintering aids. After secondary ball milling, they are dried, granulated, pressed and debinded, and finally sintered at 1050-1200℃ for 1-4h.

[0013] Beneficial effects of the present invention: The present invention provides a piezoelectric ceramic material with high Curie temperature and high piezoelectric coefficient. Although the piezoelectric coefficient of SrBi2Nb2O9 is greater than that of CaBi2Nb2O9, its Curie temperature is far less than that of CaBi2Nb2O9. 2+ and Sr 2+ As a complex A-site metal ion, Ca 2+ Replace part of Sr 2+ The unit cell volume and ion displacement polarization are then reduced, and the electric domain is stabilized, thereby increasing the Curie temperature. Both LiTaO3 and LaAlO3 are perovskite structure compounds. Currently, there are reports on the introduction of perovskite structure compounds into KNN and PZT piezoelectric ceramics, but there are no reports on the introduction of LiTaO3 or / and LaAlO3 into bismuth layered structure piezoelectric ceramics. In the present application, the moderate lattice distortion caused by the doping of LiTaO3 and LaAlO3 and the reduction of the oxygen vacancy concentration caused by the volatilization of Bi weaken the pinning effect, increase the number of reversible domains, and improve the polarizability and piezoelectric activity of the piezoelectric ceramic material, thereby achieving the effect of improving its piezoelectric properties. The introduction of sintering aids promotes the generation of moderate lattice distortion or vacancies inside the piezoelectric ceramic material, which also makes it easier for the domain wall to flip under the action of the electric field, thereby improving the polarization efficiency and further improving its piezoelectric properties. In addition, the sintering temperature can be reduced, the microstructure of the ceramic can be improved, the porosity can be reduced, and the density can be increased, thereby improving the piezoelectric properties. The piezoelectric ceramic material prepared by the present invention has a relatively high Curie temperature (above 500°C) and excellent electrochemical properties. The maximum piezoelectric constant can reach 35pC / N, which is a significant improvement compared to the currently reported bismuth layered structure piezoelectric ceramics. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a SEM photograph of the polished thermally corroded surface of the piezoelectric ceramic material in Example 1. It can be seen that the internal density is relatively high and no obvious pores are observed. DETAILED DESCRIPTION

[0015] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.

[0016] Embodiment 1: This embodiment provides a piezoelectric ceramic material with a high Curie temperature and a high piezoelectric coefficient, including 0.875Bi2Ca 0.2 Sr 0.8 Nb2O9-0.1LiTaO3-0.025LaAlO3, CuO and CeO2; Preparation method of the above piezoelectric ceramic material: Bi2O3, CaCO3, SrCO3 and Nb2O5 are mixed and added to a ball mill, and anhydrous ethanol is used as the ball milling medium. After the mixture is ball milled for 10 hours on a planetary ball mill, it is dried. The mixture is placed in a mold and pressed into tablets at 10 MPa. The tablets are then heated to 750°C at a rate of 5°C / min and pre-fired for 1 hour. After the pre-fired, the product is crushed and mixed with LiTaO3, LaAlO3, CuO and CeO2. The mixture is added to a ball mill, and anhydrous ethanol is used as the ball milling medium. The mixture is ball milled for a second time for 10 hours on a planetary ball mill and then dried. A 10wt% concentration of PVA solution is added as a binder to form granules. The granules are passed through a 120-mesh sieve and placed in a mold and pressed into blanks at a pressure of 100 MPa. The blanks are heated to 650°C at a rate of 1°C / min and kept for 1 hour for debinding. The blanks are then heated to 1100°C and kept for 2 hours.

[0017] Embodiment 2: This embodiment provides a piezoelectric ceramic material with a high Curie temperature and a high piezoelectric coefficient, including 0.875Bi2Ca 0.2 Sr 0.8 Nb2O9-0.1LiTaO3-0.025LaAlO3, CuO and CeO2; Preparation method of the above piezoelectric ceramic material: Bi2O3, CaCO3, SrCO3 and Nb2O5 are mixed and added to a ball mill, and anhydrous ethanol is used as the ball milling medium. After the mixture is ball milled for 10 hours on a planetary ball mill, it is dried. The mixture is placed in a mold and pressed into tablets at 10 MPa. The tablets are then heated to 750°C at a rate of 5°C / min and pre-fired for 1 hour. After the pre-fired, the product is crushed and mixed with LiTaO3, LaAlO3, CuO and CeO2. The mixture is added to a ball mill, and anhydrous ethanol is used as the ball milling medium. The mixture is ball milled for a second time for 10 hours on a planetary ball mill and then dried. A 10wt% concentration of PVA solution is added as a binder to form granules. The granules are passed through a 120-mesh sieve and placed in a mold and pressed into blanks at a pressure of 100 MPa. The blanks are heated to 650°C at a rate of 1°C / min and kept for 1 hour for debinding. The blanks are then heated to 1050°C and kept for 2 hours.

[0018] Embodiment 3: This embodiment provides a piezoelectric ceramic material with a high Curie temperature and a high piezoelectric coefficient, including 0.875Bi2Ca 0.2 Sr 0.8 Nb2O9-0.1LiTaO3-0.025LaAlO3, CuO and CeO2; Preparation method of the above piezoelectric ceramic material: Bi2O3, CaCO3, SrCO3 and Nb2O5 are mixed and added to a ball mill, and anhydrous ethanol is used as the ball milling medium. After the mixture is ball milled for 10 hours on a planetary ball mill, it is dried. The mixture is placed in a mold and pressed into tablets at 10 MPa. The tablets are then heated to 750°C at a rate of 5°C / min and pre-fired for 1 hour. After the pre-fired, the product is crushed and mixed with LiTaO3, LaAlO3, CuO and CeO2. The mixture is added to a ball mill, and anhydrous ethanol is used as the ball milling medium. The mixture is ball milled for a second time for 10 hours on a planetary ball mill and then dried. A 10wt% concentration of PVA solution is added as a binder to form granules. The granules are passed through a 120-mesh sieve and placed in a mold and pressed into blanks at a pressure of 100 MPa. The blanks are heated to 650°C at a rate of 1°C / min and kept for 1 hour for debinding. The blanks are then heated to 1150°C and kept for 2 hours.

[0019] Embodiment 4: This embodiment provides a piezoelectric ceramic material with a high Curie temperature and a high piezoelectric coefficient, including 0.875Bi2Ca 0.2 Sr 0.8 Nb2O9-0.1LiTaO3-0.025LaAlO3, CuO and CeO2; Preparation method of the above piezoelectric ceramic material: Bi2O3, CaCO3, SrCO3 and Nb2O5 are mixed and added to a ball mill, and anhydrous ethanol is used as the ball milling medium. After the mixture is ball milled for 10 hours on a planetary ball mill, it is dried. The mixture is placed in a mold and pressed into tablets at 10 MPa. The tablets are then heated to 750°C at a rate of 5°C / min and pre-fired for 1 hour. After the pre-fired, the product is crushed and mixed with LiTaO3, LaAlO3, CuO and CeO2. The mixture is added to a ball mill, and anhydrous ethanol is used as the ball milling medium. The mixture is ball milled for a second time for 10 hours on a planetary ball mill and then dried. A 10wt% concentration of PVA solution is added as a binder to form granules. The granules are passed through a 120-mesh sieve and placed in a mold and pressed into blanks at a pressure of 100 MPa. The blanks are heated to 650°C at a rate of 1°C / min and kept for 1 hour for debinding. The temperature is then continued to be raised to 1200°C and kept for sintering for 2 hours.

[0020] Comparative Example 1: This comparative example provides a piezoelectric ceramic material with a high Curie temperature and a high piezoelectric coefficient, and its structural formula is 0.875Bi2Ca 0.2 Sr 0.8 Nb2O9-0.1LiTaO3-0.025LaAlO3; Preparation method of the above piezoelectric ceramic material: Bi2O3, CaCO3, SrCO3 and Nb2O5 are mixed and added to a ball mill, and anhydrous ethanol is used as the ball milling medium. After the mixture is ball milled for 10 hours on a planetary ball mill, it is dried. The mixture is placed in a mold and pressed into tablets at 10 MPa. The tablets are then heated to 750°C at a rate of 5°C / min and pre-fired for 1 hour. After the pre-fired, the product is crushed and mixed with LiTaO3 and LaAlO3, added to a ball mill, and anhydrous ethanol is used as the ball milling medium. The mixture is ball milled for a second time for 10 hours on a planetary ball mill and dried. A 10wt% concentration of PVA solution is added as a binder to form granules. The granules are passed through a 120-mesh sieve and placed in a mold and pressed into blanks at a pressure of 100 MPa. The blanks are heated to 650°C at a rate of 1°C / min and kept for 1 hour for debinding. The blanks are then heated to 1100°C and kept for 2 hours.

[0021] Comparative Example 2: This comparative example provides a piezoelectric ceramic material with a high Curie temperature and a high piezoelectric coefficient, comprising 0.875Bi2Ca 0.2 Sr 0.8 Nb2O9-0.1LiTaO3-0.025LaAlO3 and CuO; Preparation method of the above piezoelectric ceramic material: Bi2O3, CaCO3, SrCO3 and Nb2O5 are mixed and added to a ball mill, and anhydrous ethanol is used as the ball milling medium. After the mixture is ball milled for 10 hours on a planetary ball mill, it is dried. The mixture is placed in a mold and pressed into tablets at 10 MPa. The tablets are then heated to 750°C at a rate of 5°C / min and pre-fired for 1 hour. After the pre-fired, the product is crushed and mixed with LiTaO3, LaAlO3 and CuO. The product is added to a ball mill, and anhydrous ethanol is used as the ball milling medium. The mixture is ball milled for a second time for 10 hours on a planetary ball mill and dried. A 10wt% concentration of PVA solution is added as a binder to form particles. The resulting particles are passed through a 120-mesh sieve and placed in a mold and pressed into blanks at a pressure of 100 MPa. The blanks are heated to 650°C at a rate of 1°C / min and kept for 1 hour for debinding. The blanks are then heated to 1100°C and kept for 2 hours.

[0022] Comparative Example 3: This comparative example provides a piezoelectric ceramic material with a high Curie temperature and a high piezoelectric coefficient, comprising 0.875Bi2Ca 0.2 Sr 0.8 Nb2O9-0.1LiTaO3-0.025LaAlO3 and CeO2; Preparation method of the above piezoelectric ceramic material: Bi2O3, CaCO3, SrCO3 and Nb2O5 are mixed and added to a ball mill, and anhydrous ethanol is used as the ball milling medium. After the mixture is ball milled for 10 hours on a planetary ball mill, it is dried. The mixture is placed in a mold and pressed into tablets at 10 MPa. The tablets are then heated to 750°C at a rate of 5°C / min and pre-fired for 1 hour. After the pre-fired, the product is crushed and mixed with LiTaO3, LaAlO3 and CeO2, and added to a ball mill, and anhydrous ethanol is used as the ball milling medium. The mixture is ball milled for a second time for 10 hours on a planetary ball mill and dried. A 10wt% concentration of PVA solution is added as a binder to form granules. The granules are passed through a 120-mesh sieve and placed in a mold and pressed into blanks at a pressure of 100 MPa. The blanks are heated to 650°C at a rate of 1°C / min and kept for 1 hour for debinding. The blanks are then heated to 1100°C and kept for 2 hours.

[0023] Comparative Example 4: The same as Example 1, except that Bi2CaNb2O9 is used instead of Bi2Ca 0.2 Sr 0.8 Nb2O9.

[0024] This comparative example provides a piezoelectric ceramic material with a high Curie temperature and a high piezoelectric coefficient, comprising 0.875Bi2CaNb2O9-0.1LiTaO3-0.025LaAlO3, CuO and CeO2 in a mass ratio of 100:0.25:0.25; Preparation method of the above piezoelectric ceramic material: Bi2O3, CaCO3 and Nb2O5 are mixed and added to a ball mill, and anhydrous ethanol is used as the ball milling medium. After the mixture is ball milled for 10 hours on a planetary ball mill, it is dried. The mixture is placed in a mold and pressed into tablets at 10 MPa. The tablets are then heated to 750°C at a rate of 5°C / min and pre-fired for 1 hour. After the pre-fired, the product is crushed and mixed with LiTaO3, LaAlO3, CuO and CeO2. The mixture is added to a ball mill, and anhydrous ethanol is used as the ball milling medium. The mixture is ball milled for a second time for 10 hours on a planetary ball mill and then dried. A 10wt% concentration of PVA solution is added as a binder to form granules. The granules are passed through a 120-mesh sieve and placed in a mold and pressed into blanks at a pressure of 100 MPa. The blanks are heated to 650°C at a rate of 1°C / min and kept for 1 hour for debinding. The blanks are then heated to 1100°C and kept for 2 hours.

[0025] Comparative Example 5: The same as Example 1, except that Bi2SrNb2O9 is used instead of Bi2Ca 0.2 Sr 0.8 Nb2O9.

[0026] This comparative example provides a piezoelectric ceramic material with a high Curie temperature and a high piezoelectric coefficient, comprising 0.875Bi2SrNb2O9-0.1LiTaO3-0.025LaAlO3, CuO and CeO2 in a mass ratio of 100:0.25:0.25; Preparation method of the above piezoelectric ceramic material: Bi2O3, SrCO3 and Nb2O5 are mixed and added to a ball mill, and anhydrous ethanol is used as the ball milling medium. After the mixture is ball milled for 10 hours on a planetary ball mill, it is dried. The mixture is placed in a mold and pressed into tablets at 10 MPa. The tablets are then heated to 750°C at a rate of 5°C / min and pre-fired for 1 hour. After the pre-fired, the product is crushed and mixed with LiTaO3, LaAlO3, CuO and CeO2. The mixture is added to a ball mill, and anhydrous ethanol is used as the ball milling medium. The mixture is ball milled for a second time for 10 hours on a planetary ball mill and then dried. A 10wt% concentration of PVA solution is added as a binder to form granules. The granules are passed through a 120-mesh sieve and placed in a mold and pressed into blanks at a pressure of 100 MPa. The blanks are heated to 650°C at a rate of 1°C / min and kept for 1 hour for debinding. The blanks are then heated to 1100°C and kept for 2 hours.

[0027] Comparative Example 6: It is basically the same as Example 1, except that LiTaO3 is not added.

[0028] Comparative Example 7: It is basically the same as Example 1, except that LaAlO3 is not added.

[0029] Performance Test: The piezoelectric ceramic materials prepared in Examples 1-4 and Comparative Examples 1-7 of the present invention were polished and then silvered, and polarized in an electric field of 7 kV / mm for 15 min in silicone oil at 100° C. and then left for one day as test samples; The high temperature dielectric temperature spectrum test system (GJW-I) was used to measure the change of the dielectric constant of the sample with temperature, and the Curie temperature Tc was determined. The ZJ-3A quasi-static d 33 The piezoelectric constant d of the test specimen is measured by the measuring instrument 33 The measurement frequency is 110 Hz, and the Agilent 4294A precision impedance analyzer is used to measure the electrical properties of the sample, such as the mechanical quality factor Qm and the planar electromechanical coupling coefficient kp.

[0030] The test results are shown in Table 1 below: ; It can be seen from Table 1 above that the piezoelectric ceramic material prepared in the present invention has a relatively high Curie temperature (above 500°C) and excellent electrochemical properties. The maximum piezoelectric constant can reach 35pC / N, which is a significant improvement compared to the currently reported bismuth layered structure piezoelectric ceramics.

[0031] By comparing the data of Examples 1-4, it can be seen that when the sintering temperature is 1100°C, the piezoelectric performance of the piezoelectric ceramic material is optimal; By comparing the data of Example 1 with Comparative Examples 1-3, it can be seen that the addition of CuO and CeO2 plays a positive role in increasing the Curie temperature of piezoelectric ceramic materials and improving piezoelectric properties; By comparing the data of Example 1 with Comparative Example 4, it can be seen that although Sr doping Bi2CaNb2O9 will cause its Curie temperature to decrease, it can improve its piezoelectric properties; By comparing the data of Example 1 with that of Comparative Example 5, it can be seen that Ca-doped Bi2SrNb2O9 plays a positive role in increasing the Curie temperature of piezoelectric ceramic materials and improving piezoelectric properties; By comparing the data of Example 1 with Comparative Examples 6-7, it can be seen that LiTaO3 and LaAlO3 can effectively improve the Curie temperature and piezoelectric properties of piezoelectric ceramic materials.

[0032] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A piezoelectric ceramic material with high Curie temperature and high piezoelectric coefficient, characterized in that: The structural formula of the piezoelectric ceramic material is as follows: (1-x-y)(Bi2O2) 2+ (A m-1 B m O 3m+1 ) 2- -xLiTaO3-yLaAlO3 Among them, A is Ca 2+ and / or Sr 2+ ; B is Nb 5+ ; m is an integer between 1 and 4; 0<x≤0.2; 0<y≤0.2; It also includes a sintering aid, which is a transition metal oxide and / or a lanthanide rare earth oxide; The transition metal oxide is manganese oxide and / or copper oxide; The lanthanide rare earth oxide is a composite of any one or more of cerium oxide, samarium oxide and dysprosium oxide; The amount of the sintering aid is (1-xy)(Bi2O2) 2+ (A m-1 B m O 3m+1 ) 2- -0.1-1% of the mass of xLiTaO3-yLaAlO3.

2. The piezoelectric ceramic material according to claim 1, characterized in that: 0.05≤x≤0.15, 0.01≤y≤0.

05.

3. The piezoelectric ceramic material according to claim 1, characterized in that: x=0.1,y=0.

025.

4. A method for preparing a piezoelectric ceramic material as claimed in any one of claims 1 to 3, characterized in that: Bi2O3, oxide A and oxide B are mixed, dried and pre-fired at 600-800℃ after ball milling once, and then mixed with LiTaO3, LaAlO3 and sintering aids. After secondary ball milling, they are dried, granulated, pressed and debinded, and finally sintered at 1050-1200℃ for 1-4h.

Citation Information

Patent Citations

  • Ca2+ doped bismuth laminated piezoceramic material and preparation method thereof

    CN101982441A

  • Sodium niobate lithium tantalate series lead-free piezoelectric ceramic composite

    CN102557635A

  • High-temperature piezoelectric ceramic for pressure sensor and preparation method of high-temperature piezoelectric ceramic

    CN118812261A

  • Piezoelectric ceramic composition

    CN1238316A

  • Composite bismuth laminated leadless piezoelectric ceramic composition

    CN1654423A

Cited By

  • Piezoceramic material and preparation method thereof

    CN121318431A